2017
DOI: 10.17219/acem/61613
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in 13-year-old adolescents with abdominal obesity, depending on the BMI value

Abstract: Background. Excessive adipocyte growth during the pubertal transition predisposes to the development and persistence of obesity in adulthood. Visceral accumulation of body fat is particularly disadvantageous when it is correlated with insulin resistance, secondary hyperinsulinaemia, dysglicaemia, and atherogenic dyslipidemia.Objectives. The aim of this study was to conduct a nutritional status assessment and body composition analysis in 13-year-old adolescents of both genders with visceral fat accumulation (WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Better correlations were found between FM, FMI with fatty liver. Another study was reported that BIA FM positive correlated to BMI, WC in obese children [23]. Our findings support these data and FM, FMI moderately positive correlated to BMI-SDS, WC, UMAC and HC in obese children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Better correlations were found between FM, FMI with fatty liver. Another study was reported that BIA FM positive correlated to BMI, WC in obese children [23]. Our findings support these data and FM, FMI moderately positive correlated to BMI-SDS, WC, UMAC and HC in obese children.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is important to determine both fat tissue location and its percentage in body composition. The visceral location of fat tissue revealed in the developmental age is a significant factor in the development of metabolic syndrome [23]. Dual-energy X-ray absorptiometry is now accepted as a reference and gold standard method for assessing body composition in children and adolescents with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescents with a normal BMI, it has been observed that a significant increase in TBF accompanied by a decrease in lean mass and total body water content may contribute to development of metabolic syndrome 3 . Furthermore, a previous meta‐analysis of observational studies in adolescents suggested that hyperinsulinaemia plays a key role in the development of metabolic disorders through increased adipose tissue function 4 …”
Section: Age Years N R P Valuementioning
confidence: 99%
“…Therefore, education about proper dietary habits, regular health care, control of body weight and regular medical examinations for adolescents are needed in particular 5 . Assessment of weight status in children and adolescents includes anthropometric measurements and indicators calculated on their basis, such as body mass index (BMI), waist-to-hip ratio (WHR) and waist-toheight ratio (WHtR), as they were shown to correlate strongly with risk factors for CVD 6 . WHtR is an indicator that reflects a relationship, changing with age, between the rate of waist circumference (WC) increase and body height.…”
Section: Introductionmentioning
confidence: 99%
“…WHtR is an indicator that reflects a relationship, changing with age, between the rate of waist circumference (WC) increase and body height. It is a simple indicator for estimating the risk factors for CVD during clinical screening, and it seems to be even more reliable than WC and BMI ( 6 ). There is growing evidence that children and adolescents with high blood pressure (BP) are much more common than previously thought.…”
Section: Introductionmentioning
confidence: 99%